Sharing a place-based indigenous methodology and learnings. Issue 7 (2nd July 2020) - Wooltorton, Sandra; Collard, Len; Horwitz, Pierre; Poelina, Anne; Palmer, David
Abstract: Building on a methodology of Cooperative Inquiry, the outcomes of five interconnected place-based learning projects from Australia are synthesised and elaborated in this paper. The methodology can facilitate the everyday living and sharing of an Earth-based consciousness: one that enriches Transformative Sustainability Education (TSE) through recognising meanings and stories in landscape, and celebrates Indigenous ways of knowing, being and doing. Indigenous-led environmental education is shown to link with one of the longest continuous environmental education systems in the world and it is contended that because of its ongoing history, environmental education carries a cultural obligation. In Australia, every landscape is Indigenous and storied, and all Australians have an inherent right to learn that joy in place, along with the responsibility to care for it. Teaching and learning a relationship with place as family, is one way that environmental education can lead that campaign. This place-based methodology is a lifetime commitment involving everyday actions for change, a whole-of-education dedication.